Respuesta :
The answer:
Q1: a binomial of degree 100:
for example: x^100 + 2 (it is called binomial because the number of term is 2: x^100 and 2)
Q2: the coefficients:
the main rule is:
if we have P(x)= a1X^p + a2X^p-1+ .... + a0 as polynomial, so the coefficients are (a1, a2, ... ao)
i) x3 in 2x + x2 – 5x3 + x4, the coefficient is -5
ii) x2 in (π/3) x2 + 7x – 3, the coefficient is (π/3)
iii) x in √3 - 2√2x + 4x2, the coefficient is - 2√2
Q3. If p(y) = 4 + 3y – y2 + 5y3, (i) p(0) can be found with
(i) p(0) = 4 + 3*0 – 0² + 5*0^3= 4, p(0)= 4, the same method to p(2)
ii) p(2)=4 + 3*2– 2² + 5*2^3=49, p(2)=49
iii) p(-1)= 4 + 3*(-1) – (-1)² + 5*(-1)^3 = -5, p(-1)= -5
Q4. the zero of the polynomial
i) h(x) = 6x-1, to find it, just egalize h(x) to 0, 6x-1 =0, it implies 6x=1, and x=1/6, so the zero is x=1/6
ii) p(t) = 2t-3, ii) p(t) = 2t-3=0 implies 2t=3 and the zero is t=3/2
the remainder in each case if p(x) is divided by g(x)
(i) p(x) = x3 – 6x2 + 2x – 4, g(x) = 1 – 2x
x3 – 6x2 + 2x – 4
R(x) = ------------------------ = (-x²/2 + 11x/4 + 3/8) - 35 / 8(-2x + 1)
1 – 2x
so the remainder is - 35 / 8
(ii) p(x) = 2x3 – 5x2 + 4x – 3, g(x) = 3x + 1.
2x3 – 5x2 + 4x – 3
R(x) = -------------------------- = 2x²/3 -17x /9 +53/27 - 134 /27(3x+1)
3x + 1
the remainder is - 134 /27
Q1: a binomial of degree 100:
for example: x^100 + 2 (it is called binomial because the number of term is 2: x^100 and 2)
Q2: the coefficients:
the main rule is:
if we have P(x)= a1X^p + a2X^p-1+ .... + a0 as polynomial, so the coefficients are (a1, a2, ... ao)
i) x3 in 2x + x2 – 5x3 + x4, the coefficient is -5
ii) x2 in (π/3) x2 + 7x – 3, the coefficient is (π/3)
iii) x in √3 - 2√2x + 4x2, the coefficient is - 2√2
Q3. If p(y) = 4 + 3y – y2 + 5y3, (i) p(0) can be found with
(i) p(0) = 4 + 3*0 – 0² + 5*0^3= 4, p(0)= 4, the same method to p(2)
ii) p(2)=4 + 3*2– 2² + 5*2^3=49, p(2)=49
iii) p(-1)= 4 + 3*(-1) – (-1)² + 5*(-1)^3 = -5, p(-1)= -5
Q4. the zero of the polynomial
i) h(x) = 6x-1, to find it, just egalize h(x) to 0, 6x-1 =0, it implies 6x=1, and x=1/6, so the zero is x=1/6
ii) p(t) = 2t-3, ii) p(t) = 2t-3=0 implies 2t=3 and the zero is t=3/2
the remainder in each case if p(x) is divided by g(x)
(i) p(x) = x3 – 6x2 + 2x – 4, g(x) = 1 – 2x
x3 – 6x2 + 2x – 4
R(x) = ------------------------ = (-x²/2 + 11x/4 + 3/8) - 35 / 8(-2x + 1)
1 – 2x
so the remainder is - 35 / 8
(ii) p(x) = 2x3 – 5x2 + 4x – 3, g(x) = 3x + 1.
2x3 – 5x2 + 4x – 3
R(x) = -------------------------- = 2x²/3 -17x /9 +53/27 - 134 /27(3x+1)
3x + 1
the remainder is - 134 /27
Answer:The answer:
Q1: a binomial of degree 100:
for example: x^100 + 2 (it is called binomial because the number of term is 2: x^100 and 2)
Q2: the coefficients:
the main rule is:
if we have P(x)= a1X^p + a2X^p-1+ .... + a0 as polynomial, so the coefficients are (a1, a2, ... ao)
i) x3 in 2x + x2 – 5x3 + x4, the coefficient is -5
ii) x2 in (π/3) x2 + 7x – 3, the coefficient is (π/3)
iii) x in √3 - 2√2x + 4x2, the coefficient is - 2√2
Q3. If p(y) = 4 + 3y – y2 + 5y3, (i) p(0) can be found with
(i) p(0) = 4 + 3*0 – 0² + 5*0^3= 4, p(0)= 4, the same method to p(2)
ii) p(2)=4 + 3*2– 2² + 5*2^3=49, p(2)=49
iii) p(-1)= 4 + 3*(-1) – (-1)² + 5*(-1)^3 = -5, p(-1)= -5
Q4. the zero of the polynomial
i) h(x) = 6x-1, to find it, just egalize h(x) to 0, 6x-1 =0, it implies 6x=1, and x=1/6, so the zero is x=1/6
ii) p(t) = 2t-3, ii) p(t) = 2t-3=0 implies 2t=3 and the zero is t=3/2
the remainder in each case if p(x) is divided by g(x)
(i) p(x) = x3 – 6x2 + 2x – 4, g(x) = 1 – 2x
x3 – 6x2 + 2x – 4
R(x) = ------------------------ = (-x²/2 + 11x/4 + 3/8) - 35 / 8(-2x + 1)
1 – 2x
so the remainder is - 35 / 8
(ii) p(x) = 2x3 – 5x2 + 4x – 3, g(x) = 3x + 1.
2x3 – 5x2 + 4x – 3
R(x) = -------------------------- = 2x²/3 -17x /9 +53/27 - 134 /27(3x+1)
3x + 1
the remainder is - 134 /27
Read more on Brainly.com - https://brainly.com/question/4131444#readmore
Step-by-step explanation: